Children’s total blindness as a risk factor for early parent-child relationships: preliminary findings from an Italian sample - Gui, Anna; Perelli, Debora; Rizzo, Giulia; Ferruzza, Emilia; Mercuriali, Elena (Frontiers in Psychology, 2023)
Background: Vision provides crucial information for parent-child attunement that scaffolds social development from the first months of life. Congenital blindness might affect both parental well-being and children’s behavior during parent-child interaction. In this study, we compared families of young children with total versus partial blindness to understand the link between residual vision, parenting stress and perceived social support, and children’s behavior during parent-child interaction. Methods: Participants were forty-two white parents (21 fathers and 21 mothers) and their congenitally blind children (14 females, mean age=14.81 months, SD=10.46) with no co-occurring disability, recruited at the Robert Hollman Foundation rehabilitation centers in Italy. Parents’ scores on the Parenting Stress Index and Multidimensional Scale of Perceived Social Support questionnaires, as well as children’s behaviors signaling joint engagement during video-recorded episodes of parent-child interaction, were compared between the Total Blindness (TB, n=12 children with no light perception or light perception in the dark but no quantifiable visual acuity) and Partial Blindness (PB, n=9 children with a residual visual acuity below 3/60) groups. Results: We found that parents of TB children had higher parenting stress and lower perceived social support scores than parents of PB children. In fathers, total stress and stress linked to perceiving the child as difficult negatively correlated with perceived support from friends. There was no difference in the time TB and PB children spent displaying joint engagement behaviors during parent-child interaction. However, TB children directed their gaze and face less often towards their parents than PB children. We observed a trend of association between this behavior and maternal stress. Conclusions: These preliminary results suggest that the complete absence of vision from birth has adverse effects on stress linked to parenting and parental perceived social support. These findings support the importance of early family-centered interventions that extend to the parents’ communities and facilitate the parent-child dyad’s communication through non-visual behaviors. Replication is warranted in larger and more diverse samples.